DEVELOPMENT OF CHARACTER ASSESSMENT INSTRUMENTS IN SERVICE-LEARNING AT BIOLOGY EDUCATION DEPARTMENT SANATA DHARMA UNIVERSITY - Handoyo, Luisa Diana; Listyarini, Ika Yuli (Sanata Dharma University Yogyakarta, 2018)
Service-learning is one of the learning methods that combine learning in the classroom with service activities to the community. In service-learning, students are invited to apply the lecture material in solving the problems in the community directly. In the process, many student characters will be trained and developed. This research focuses on developing character assessment instruments that develop after the implementation of service-learning activities in Biology Education Program, Sanata Dharma University, Yogyakarta. The purpose of this research is to develop a character assessment instrument in the form of questionnaires for students, especially in Biology Education at Sanata Dharma University. Questionnaires developed through the stages of the development of the instrument, including determining the purpose of the preparation of the instrument, find the relevant theory, compile instrument indicators, compile instrument, content validation, and revisions based on input validator. Instrument validation is done through content validation with expert judgment. Based on the result of content validation by expert judgment, Aiken index is obtained at 0.85 with high validation category. Based on these results, the character assessment questionnaire developed can be implemented in the learning to assess the character development of students after implementing service-learning.Â DOI:Â http://e-journal.usd.ac.id/index.php/IJIET/article/view/957/749